Converging Sustainable Entrepreneurship and the Contemporary Marketing Practices. An Insight into Romanian Start-Ups - Cristian Valentin Hapenciuc; Florina Pînzaru; Elena-Mădălina Vătămănescu; Pavel Stanciu (Amfiteatru Economic Journal, 2015)
Over the past years, the issue of sustainable entrepreneurship has coagulated multiple research interests due to the fact that it integrates three main pillars, namely human resource management (people) and the concerns for planet protection and for the economic effectiveness sustained by profit. The rapid social and economic transformations have imposed the assumption of an integrative perspective, especially to the organizations oriented to ensure their viability on the market and industry. Hereby, researchers believe that such an approach should be indicative of start-ups which should advance feasible solutions to market imperfections through innovative products and services and through effective marketing models. Against this backdrop, the present paper aims to investigate the correlations between sustainable entrepreneurship and the marketing types articulated by the Contemporary Marketing Practices (CMP) research program, relying on a questionnaire-based survey conducted with 104 start-up entrepreneurs in Romania. As the findings show, the discussed marketing types often discretionary correlate in practice with the most important dimension of sustainability that is people.
Keywords: M31; Q56; 330; Sustainable entrepreneurship; Contemporary Marketing Practices; Start-ups; People - environment - profit; Entrepreneurial marketing